2016
DOI: 10.2147/jpr.s118945
|View full text |Cite
|
Sign up to set email alerts
|

Risks associated with borrowing and sharing of prescription analgesics among patients observed by pain management physicians in Croatia: a qualitative study

Abstract: BackgroundUnderstanding and improving patient safety is a key issue in medicine. One of the potential threats to patient safety is the sharing of medication among patients, which is a form of self-medication. This study analyzed experiences and attitudes of pain management physicians (PMPs) about sharing prescription analgesics among patients.MethodsThis qualitative study was conducted by semi-structured interviews among PMPs employed in Croatian pain clinics. The study involved two researchers and 15 PMPs.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…In line with previous studies, the main four motives quoted for borrowing or lending prescription medications were ‘having the same problem as the person’, ‘running out of previously prescribed medicines’, ‘the problem wasn’t serious enough to go to the doctor’ and ‘having leftovers that would have gone to waste’. However, other studies have shown that unusual situations when professional help is not available, distrust in physicians, inconvenience of contacting a physician, availability of a drug with person nearby, financial saving were potential reasons for sharing prescription medications …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies, the main four motives quoted for borrowing or lending prescription medications were ‘having the same problem as the person’, ‘running out of previously prescribed medicines’, ‘the problem wasn’t serious enough to go to the doctor’ and ‘having leftovers that would have gone to waste’. However, other studies have shown that unusual situations when professional help is not available, distrust in physicians, inconvenience of contacting a physician, availability of a drug with person nearby, financial saving were potential reasons for sharing prescription medications …”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, painkillers, antibiotics and allergy medicine were the most frequently borrowed and lent medicines . This is possibly because, in Saudi Arabia, allergy medications and some pain medications are easily accessible and can be obtained either with or without a prescription over the counter (OTC).…”
Section: Discussionsupporting
confidence: 86%
“…Our recent study about opinions of pain management physicians regarding sharing of prescription analgesics among patients showed that majority of them believe that this is a negative behavior and that patients should be educated about its dangers. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Negative aspects include delayed seeking of medical care, increased risk of side effects, health complications associated with incorrect medication or multiplied risk of developing resistance to medication (Goldsworthy and Mayhorn, ; Dimitrov et al., ; Beyene et al., ). Justifiable aspects of this behaviour, as described in literature, include situations where medical aid is unavailable, inconvenience associated with contacting a physician, saving money, lack of faith in physicians, helping patients cope with pain, accessibility of drugs in pharmacies, availability of medication provided by close individuals and maintaining good interpersonal relationships (Hodgetts et al., ; Kamutingondo et al., ; Beyene et al., ; Markotic and Puljak, ; Markotic et al., ). Nonrecreational sharing of medication is mostly motivated by the desire to help others or oneself (Kamutingondo et al., ; Markotic et al., ).…”
Section: Introductionmentioning
confidence: 99%